2018
DOI: 10.20944/preprints201811.0377.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Acute Exacerbation of Idiopathic Pulmonary Fibrosis

Abstract: Idiopathic Pulmonary Fibrosis (IPF) is most common idiopathic interstitial pneumonias. IIPF is often seen in elderly smoker man. Diagnosis of IPF is integration of detailed clinical history, specific physical examination, laboratory findings, pulmonary function test, chest high-resolution computed tomography (HRCT) and pathology. IPF have heterogeneous clinical course from asymptomatic stable state to progressive respiratory failure or acute exacerbation (AE). AE of IPF have several important differential diag… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…Several studies have given eloquent proof that IPAF is associated with age, female sex, and smoking status [4,7,[50][51][52][53][54]. In addition, our group et al found that KL-6 can re ect the progression of the disease and play a key role in re ecting the degree of lung epithelial cell injury and brosis in IPAF.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Several studies have given eloquent proof that IPAF is associated with age, female sex, and smoking status [4,7,[50][51][52][53][54]. In addition, our group et al found that KL-6 can re ect the progression of the disease and play a key role in re ecting the degree of lung epithelial cell injury and brosis in IPAF.…”
Section: Discussionmentioning
confidence: 82%
“…Several studies have given eloquent proof that IPAF is associated with age, female sex, and smoking status. 4,7,[25][26][27][28][29] In addition, we also found that KL-6 can reflect the disease progression and play a key role in the display of the degree of lung epithelial cell injury and fibrosis in patients with IPAF. In spite of MMPs combined with clinical risk factors that could detect the presence of IPAF in this study, it should be noted that MMP-7 and MMP-12 were weak differences between IPAF and IPF cohorts.…”
Section: Pulmonary Function Tests (Pfts) and Blood Cell Testmentioning
confidence: 81%
“…It was also suggested that honeycombing with predilection to the anterior upper lobe is distinctive of RA-ILD with UIP or UIP/NSIP mixed pattern. In SSc-ILD and PM/DM-ILD, the most predominant pattern was fibrosing NSIP without honeycombing (116).…”
Section: What Are the Radiologic Differences Between Idiopathic Ild A...mentioning
confidence: 99%
“…The chest radiograph is easy to use and cost effective in clinical practice, as an alternative to HRCT, and provides useful new information for clinicians. Regarding the role of the chest radiograph for IPF patients, both distribution of fibrosis and volume loss of the bilateral lower lung field have been addressed [ 24 , 25 ]. Chest HRCT has played a major role in the diagnosis and treatment response of IPF patients [ 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%